Answer:
uyjytyhy
Step-by-step explanation:
tthtyi
tyujftyu
yijy
B! If you draw the line of symmetry diagonally, you have two triangles
(f∘g)(x) is equivalent to f(g(x)). We solve this problem just as we solve f(x). But since it asks us to find out f(g(x)), in f(x), each time we encounter x, we replace it with g(x).
In the above problem, f(x)=x+3.
Therefore, f(g(x))=g(x)+3.
⇒(f∘g)(x)=2x−7+3
⇒(f∘g)(x)=2x−4
Basically, write the g(x) equation where you see the x in the f(x) equation.
f∘g(x)=(g(x))+3 Replace g(x) with the equation
f∘g(x)=(2x−7)+3
f∘g(x)=2x−7+3 we just took away the parentheses
f∘g(x)=2x−4 Because the −7+3=4
This is it
g∘f(x) would be the other way around
g∘f(x)=2(x+3)−7
now you have to multiply what is inside parentheses by 2 because thats whats directly in front of them.
g∘f(x)=2x+6−7
Next, +6−7=−1
g∘f(x)=2x−1
Its a lts easier than you think!
Hope this helped
If two chords intersect in a circle, then the products of the measures of the segments of the chords are equal.
I'm assuming that number up top is an 8. It's kind of blurry.
Since ten is a chord, and x is a segment of it, it can be expressed as x and 10 - x.
3(8) = x(10 - x)
(x - 6)(x - 4) = 0
x - 6 = 0 .... x - 4 = 0
x = 6 .... x = 4
4 or 6